2008
DOI: 10.1089/end.2007.0257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tamsulosin in Preventing Ureteral Stent-Related Morbidity: A Prospective Study

Abstract: Our findings indicate that administration of tamsulosin has a positive effect on stent-related urinary symptoms and QoL. Further clinical research in this area is warranted to better define the role of alpha(1)-blockers in current clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 23 publications
2
43
2
Order By: Relevance
“…Damiano et al 15 and Wang et al 8 have shown tamsulosin to be an efficacious therapy for stent-related symptoms. Usual care medication administration was used in our study and we found 65% of patients in the placebo group and 55% of patients in the lidocaine group were on tamsulosin.…”
Section: Discussionmentioning
confidence: 99%
“…Damiano et al 15 and Wang et al 8 have shown tamsulosin to be an efficacious therapy for stent-related symptoms. Usual care medication administration was used in our study and we found 65% of patients in the placebo group and 55% of patients in the lidocaine group were on tamsulosin.…”
Section: Discussionmentioning
confidence: 99%
“…Then another two studies elucidating the efficacy of alfuzosin and tamsulosin on stent symptoms were performed by Buddingfield et al and Damino et al, respectively (5, 6). Meta-analyses also showed that α-blockers are associated with improvements in stent symptoms (16, 17).…”
Section: Discussionmentioning
confidence: 99%
“…The results in the second two weeks with the stent in situ further indicated the efficacy of Doxazosin Oral Intake Therapy on stent symptoms, which were less dependent on patient surgical complications, preoperative condition and postoperative recovery. The outcomes obtained at 4 weeks after stent withdrawal were proposed to be the baseline data without the impact of ureteral calculi and related hydronephrosis (6). However, we still noted a trend for higher abdominal pain in the placebo group after stent removal; this finding might demonstrate the residual effects of the treatment or the prevalence of symptoms in background population (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two trials using oral alfuzosin, there was a statistically significant positive impact on urinary symptoms, pain, physical activity, and sleep [17,18]. In two additional studies reporting the use of the α-receptor blocker tamsulosin, Damiano et al [19] and Wang et al [20•] found significantly decreased pain and urinary symptoms while improving quality of life compared with placebo controls.…”
Section: Oral Systemic Medicationsmentioning
confidence: 99%